2012
DOI: 10.1111/j.1471-0307.2012.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of free amino acids and volatile components in three fermented milks

Abstract: Free amino acids (FAAs) and volatile components were analysed in commercial samples of yoghurt and Actimel® drink as well as laboratory‐made kefir. The lysine and cysteine were the principal amino acids and accounted for about 70% of the total FAAs in all the samples. However, the amino acid profiles in the different fermented milk products differed: on the whole values for most of the amino acids were observed to be significantly higher in the Actimel® samples. A total of 50 volatile components were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 17 publications
6
28
0
Order By: Relevance
“…Although acetone is naturally present in milk, yoghurt bacteria can produce additional amounts [3,18]. In general, the composition of the volatile profiles of the strains under study resembles both qualitatively and quantitatively those reported recently in similar works [22,50].…”
Section: Discussionsupporting
confidence: 55%
“…Although acetone is naturally present in milk, yoghurt bacteria can produce additional amounts [3,18]. In general, the composition of the volatile profiles of the strains under study resembles both qualitatively and quantitatively those reported recently in similar works [22,50].…”
Section: Discussionsupporting
confidence: 55%
“…bulgaricus and Streptococcus thermophilus in the milk medium. These 2 strains establish a symbiotic relationship in milk and perform biochemical reactions that lead to a decrease in pH and the formation of a semisolid texture and a distinctive yogurt flavor (Irigoyen et al, 2012). Promising probiotic strains, including Bacillus, Enterococcus, Escherichia, and Propionibacterium genera, and the yeast genus Saccharomyces, have been adopted in new yogurt products (Ceapa et al, 2013;Kanmani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In order to better identify the occurrence of volatiles derived from the emulsifiers, in this work a basic formulation was used and gelato samples were prepared without the addition of any flavouring agents. Thus, the expected volatiles were mainly those probably related to the milk fat fraction and processing (Irigoyen et al 2012). A total of 24 gas-chromatographic signals, obtained by the triphasic fiber, were found within this study and reported in Table 3 along with the calculated retention indexes and the retention indexes from the literature, while semi-quantification data are reported in Table 4.…”
Section: Volatile Compound Analysismentioning
confidence: 69%